Resin composition, molding material, multilayer structure, molded body, food package, resin composition and method for manufacturing multilayer structure

By adding titanium compounds and specific metal compounds to an ethylene-modified PVA resin, the thermal stability of the resin composition is significantly improved, addressing the limitations of existing PVA resin compositions in heat molding and applications requiring thermal resistance.

JP2025044179APending Publication Date: 2025-04-01MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024161149
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-19
Filing Date
2024-09-18
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing polyvinyl alcohol (PVA) resin compositions face challenges with thermal stability, as their melting point and thermal decomposition temperature are close, making heat molding difficult and limiting their applications.

Method used

Incorporating a trace amount of titanium compounds and a metal compound from the fourth period d block of the periodic table, such as zinc compounds, into an ethylene-modified PVA resin composition, which improves thermal stability by stabilizing the PVA resin structure.

Benefits of technology

The resulting resin composition exhibits excellent thermal stability, with improved resistance to thermal decomposition and coloration, enhancing its suitability for various applications including food packaging and molded products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044179000001
    Figure 2025044179000001
  • Figure 2025044179000002
    Figure 2025044179000002
  • Figure 2025044179000003
    Figure 2025044179000003
Patent Text Reader

Abstract

To provide a resin composition which is excellent in heat stability.SOLUTION: A resin composition contains a polyvinyl alcohol resin, a titanium compound, and a metal compound belonging to d block of the fourth period of the long form periodic table, where the polyvinyl alcohol resin is an ethylene modified polyvinyl alcohol resin containing 1 to 19 mol% of an ethylene structural unit, and a metal conversion content of the titanium compound is 0.0001 to 2 ppm with respect to the mass of the resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing a polyvinyl alcohol resin, a molding material, a multilayer structure, a resin composition, and a method for producing a multilayer structure. [Background technology]

[0002] Polyvinyl alcohol resin (hereinafter sometimes referred to as "PVA resin") is one of the few crystalline water-soluble polymers that has excellent film-forming properties, transparency, strength properties, and surface activity. Therefore, it is widely used in paper modifiers such as paper coating agents and paper inner application agents, adhesives for paper, wood, and inorganic materials, stabilizers for emulsion polymerization and suspension polymerization, optical films, etc.

[0003] However, PVA resins generally have problems with thermal stability, such as the melting point being very close to the thermal decomposition temperature, making them difficult to process through hot melt molding, and so they have traditionally been used in a water-soluble state.

[0004] In order to improve the thermal stability, for example, Patent Document 1 proposes an ethylene-modified PVA resin that has a specific degree of polymerization and a specific degree of saponification, has a predetermined amount of carboxy groups and lactone rings, and contains 2 to 19 mol % of ethylene structural units.

[0005] Furthermore, Patent Document 2 proposes a PVA resin having a viscosity average degree of polymerization of a specific amount or more and containing a titanium compound in an amount of 5 to 500 ppm relative to the PVA resin in order to improve the wet heat resistance.

[0006] Furthermore, Patent Document 3 proposes a PVA polymer film containing at least one metal element selected from the group consisting of transition metals and aluminum, in order to obtain a PVA polymer film that has excellent slip properties, suppresses the occurrence of wrinkles even when wound into a long film roll, is less likely to be discolored, and has excellent transparency. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-309607 A [Patent Document 2] Japanese Patent Application Publication No. 5-222609 [Patent Document 3] International Publication No. 2013 / 146533 Summary of the Invention [Problem to be solved by the invention]

[0008] According to the studies of the present inventors, the technique disclosed in the above-mentioned Patent Document 1 has a certain effect on thermal stability, but the thermal stability is still insufficient and there is room for improvement.

[0009] In addition, the technology disclosed in Patent Document 2 improves moist heat resistance by incorporating 5 to 500 ppm of titanium into the PVA resin, but if the amount is less than 5 ppm, the crosslinking effect is low and high moist heat resistance cannot be obtained.

[0010] Furthermore, the technology disclosed in Patent Document 3 uses an unmodified PVA resin and further contains a titanium compound, but the thermal stability is still insufficient and there is room for improvement.

[0011] In view of the above circumstances, an object of the present invention is to provide a resin composition having excellent thermal stability. [Means for solving the problem]

[0012] However, the present inventors have conducted extensive research in light of the above circumstances and have found that a resin composition having excellent thermal stability can be obtained by incorporating a trace amount of a titanium compound and a metal compound (excluding titanium compounds) belonging to the d block of Period 4 of the long form periodic table into an ethylene-modified PVA resin.

[0013] That is, the present invention has the following aspects. [1] A resin composition containing a PVA resin, a titanium compound, and a metal compound belonging to the d block of the long-form periodic table of the fourth period (excluding titanium compounds), The PVA resin is an ethylene-modified PVA resin containing 1 to 19 mol% of ethylene structural units, A resin composition, wherein the content of the titanium compound in terms of metal is 0.0001 to 2 ppm based on the mass of the resin composition. [2] The resin composition according to [1], wherein the content of the metal compound belonging to d block of Period 4 of the long form periodic table in terms of metal is 0.0001 to 1 ppm by mass of the resin composition. [3] The resin composition according to [1] or [2], wherein the metal compound belonging to the d block of the 4th period of the long form periodic table is a zinc compound. [4] The resin composition according to any one of [1] to [3], wherein the content of the titanium compound in terms of metal is 0.0001 ppm or more and less than 1 ppm based on the mass of the resin composition. [5] A molding material comprising the resin composition according to any one of [1] to [4]. [6] A multilayer structure having a layer containing the resin composition according to any one of [1] to [4]. [7] A molded article comprising the multilayer structure described in [6]. [8] A food packaging body comprising the multilayer structure described in [6]. [9] A method for producing the resin composition according to any one of [1] to [4], A method for producing a resin composition, comprising the step of melt-mixing a resin composition raw material containing the PVA resin and a titanium compound.

[10] A method for producing the multilayer structure according to [6], comprising the steps of: A method for producing a multilayer structure, comprising: melt-molding a layer containing the resin composition. Effect of the Invention

[0014] The resin composition of the present invention has excellent thermal stability. Furthermore, a molding material, a molded article, a food packaging article, and a multilayer structure having a layer containing the resin composition of the present invention also have excellent thermal stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described below based on examples of the mode for carrying out the present invention. However, the present invention is not limited to the embodiment described below.

[0016] In this specification, "x and / or y (x and y are optional configurations)" means at least one of x and y, and means three possibilities: x only, y only, and x and y. When expressed as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably more than X" or "preferably less than Y". When it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably more than X" or "preferably less than Y". In the present specification, the upper limit or lower limit of a numerical range described in stages can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In addition, in the numerical range described in this specification, the upper limit or lower limit of the numerical range can be replaced with a value shown in the examples. In this specification, the term "layer" includes not only a thick layer but also a relatively thin layer such as a "film," a "tape," or a "sheet."

[0017] <Resin composition> A resin composition according to one embodiment of the present invention (hereinafter, sometimes referred to as "the resin composition") contains a PVA resin as a main component, a metal compound belonging to the d block of the long form periodic table of the fourth period, and a specific trace amount of a titanium compound. That is, the base resin of the present resin composition is a PVA resin, and the content of the PVA resin in the present resin composition is usually 70 mass% or more, preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more. Each component will be described below.

[0018] [PVA resin] The PVA resin used in the present embodiment is an ethylene-modified PVA resin having an ethylene structural unit, and is usually obtained by copolymerizing a vinyl ester monomer and ethylene in the presence of a polymerization initiator and then saponifying the copolymer.

[0019] Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate. Among these, vinyl acetate is preferred from the viewpoint of obtaining a PVA resin. These monomers can be used alone or in combination of two or more. Furthermore, the monomer may be a copolymer of one or more vinyl ester monomers and other monomers copolymerizable therewith. As the other monomers copolymerizable therewith, any conventionally known monomers can be used. The content of the structural unit derived from the other copolymerizable monomer is usually preferably 15 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less, based on the PVA resin, and may not be contained.

[0020] As a polymerization method for copolymerizing the ethylene and the vinyl ester monomer in the presence of a polymerization initiator, any known polymerization method can be used, for example, bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc., but the polymerization is usually carried out by a bulk polymerization method or a solution polymerization method in which polymerization is carried out without a solvent or in a solvent such as alcohol.

[0021] The alcohol used as a solvent in solution polymerization is usually a lower alcohol such as methanol, ethanol, propanol, etc. These may be used alone or in combination of two or more kinds.

[0022] Examples of the polymerization initiator include known initiators such as azo initiators or peroxide initiators, such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethyl-valeronitrile), benzoyl peroxide, and n-propyl peroxydicarbonate. The polymerization reaction temperature is selected from the range of 0 to 150°C. These can be used alone or in combination of two or more kinds.

[0023] Saponification can be carried out by a known method, and is usually carried out by dissolving the obtained copolymer in alcohol or dimethyl sulfoxide in the presence of a saponification catalyst. Examples of saponification solvents include methanol, methyl acetate, dimethyl sulfoxide, and dimethylformamide. These can be used alone or in combination of two or more.

[0024] As the saponification catalyst, for example, an alkaline substance such as potassium hydroxide or sodium hydroxide can be used. These can be used alone or in combination of two or more kinds.

[0025] The saponification degree of the PVA resin is usually 90 to 99.99 mol%, preferably 95 to 99.5 mol%, and more preferably 97 to 99 mol%. When the saponification degree is equal to or higher than the lower limit, the PVA resin tends to have better gas barrier properties, thermal stability, moisture resistance, etc. On the other hand, when the saponification degree is equal to or lower than the upper limit, the PVA resin tends to be less susceptible to thermal degradation. The degree of saponification of such a PVA resin can be measured based on JIS K6726.

[0026] The content of the ethylene structural unit in the PVA resin is usually 1 to 19 mol%, preferably 2 to 15 mol%, and more particularly preferably 3 to 10 mol%. When the content of the ethylene structural unit is equal to or less than the upper limit, the gas barrier property and thermal stability tend to be excellent. On the other hand, when the content of the ethylene structural unit is equal to or more than the lower limit, the gas barrier property under high humidity and the melt moldability tend to be excellent.

[0027] The content of the ethylene structural unit of the PVA resin was determined from proton NMR of polyvinyl ester containing an ethylene structural unit, which is a precursor of the PVA resin. That is, the obtained polyvinyl ester was thoroughly purified by reprecipitation with n-hexane / acetone three or more times, and then dried under reduced pressure at 80°C for three days to prepare a polyvinyl ester for analysis. The polyvinyl ester was dissolved in DMSO-D and measured at 80°C using a 500MHz proton NMR (JEOLGX-500). The content of the ethylene structural unit can be calculated using a signal (4.7 to 5.2 ppm) derived from the main chain methine of the vinyl ester and a signal (0.8 to 1.6 ppm) derived from the main chain methylene of ethylene, vinyl ester, and the third component.

[0028] The melting point of the PVA resin is usually 100 to 270° C., preferably 120 to 250° C., and more preferably 150 to 230° C. If the melting point is equal to or higher than the lower limit, the resin tends to have excellent heat resistance. On the other hand, if the melting point is equal to or lower than the upper limit, the resin tends to be less susceptible to thermal degradation.

[0029] [Titanium compounds] Examples of the titanium compound used in the present embodiment include inorganic titanium compounds and organic titanium compounds. The titanium compounds may be used alone or in combination of two or more. Among these, inorganic titanium compounds are preferred.

[0030] Examples of the inorganic titanium compound include titanium oxide, titanium hydroxide, titanium chloride, and inorganic salts of titanium. Examples of the titanium oxide include titanium oxide (II), titanium oxide (III), titanium oxide (IV), and titanium suboxide. Examples of the titanium hydroxide include titanium(I) hydroxide and titanium(II) hydroxide. Examples of the titanium chloride include titanium(I) chloride and titanium(II) chloride. The inorganic salt of titanium is one other than the titanium chloride, and examples thereof include titanium phosphate, titanium sulfate, etc. Among them, titanium oxide is preferable, titanium(IV) oxide is more preferable, and rutile-type titanium(IV) oxide is particularly preferable.

[0031] Examples of the organic titanium compound include titanium carboxylates such as titanium acetate, titanium butyrate, and titanium stearate.

[0032] In addition, the titanium compound may exist in the resin composition as a titanium compound, or may exist in an ionized state or in the form of a complex interacting with the PVA resin or other ligands.

[0033] The average particle size of the titanium compound is usually 0.001 to 100 μm, preferably 0.01 to 50 μm, and more preferably 0.015 to 20 μm. When the average particle size of the titanium compound is within the above range, the thermal stability tends to be further improved. The average particle size here refers to the median diameter.

[0034] The content of the titanium compound in terms of metal is 0.0001 to 2 ppm, preferably 0.0001 to 1 ppm, more preferably 0.001 ppm or more and less than 1 ppm, and even more preferably 0.01 to 0.5 ppm, based on the mass of the resin composition. When the content of the titanium compound is equal to or more than the lower limit, the resin composition tends to have excellent thermal stability, and when the content is equal to or less than the upper limit, the resin composition tends to be less susceptible to thermal decomposition and less susceptible to coloration.

[0035] The metal-equivalent content of the titanium compound can be quantified by weighing the resin composition into a platinum crucible, incinerating it using a burner and an electric furnace, decomposing the incinerated product by heating it with nitric acid and hydrofluoric acid, treating it with a mixed acid of dilute nitric acid and dilute hydrofluoric acid, and measuring the titanium in the constant volume solution obtained by constant volume measurement using an ICP mass spectrometer (Agilent Technologies, Agilent 8800) by ICP mass spectrometry.

[0036] It is speculated that the thermal decomposition of PVA resin is caused by the formation of a polyene structure in the main chain under alkaline conditions or due to a dehydration reaction initiated by an OH group in the PVA resin. In this resin composition, the titanium in the titanium compound is stable as a tetravalent ion, so that when a polyene structure is formed in the main chain of the PVA resin, titanium is coordinated to the double bond of the polyene structure to form a chelate, which is thought to stabilize the polyene structure. Even if the amount of titanium coordinated here is small, it is speculated that it suppresses the further formation of the polyene structure, and as a result, the thermal decomposition of the PVA resin is also suppressed.

[0037] [Long-form metal compounds belonging to the d block of Period 4 of the Periodic Table (excluding titanium compounds)] Examples of metal compounds (excluding titanium compounds, the same applies below) belonging to the d block of the long periodic table, period 4 (hereinafter sometimes referred to as the "specific d block") used in this embodiment include scandium compounds, vanadium compounds, chromium compounds, manganese compounds, cobalt compounds, nickel compounds, copper compounds, zinc compounds, iron compounds, etc. Among these, manganese compounds, nickel compounds, zinc compounds, and iron compounds are preferred, and zinc compounds are particularly preferred in that the effects of the invention can be easily obtained.

[0038] Examples of the metal compound belonging to the specific periodic d block include salts and oxides of the metals belonging to the specific periodic d block. Among them, metal oxides and metal salts belonging to the specific periodic d block are preferred from the viewpoints of economy and dispersibility. In particular, metal salts belonging to the specific periodic d block are preferred from the viewpoints of ease of obtaining the effects of the invention.

[0039] Examples of the metal oxide belonging to the specific periodic d-block include chromium oxide, cobalt oxide, vanadium oxide, zinc oxide, manganese oxide, nickel oxide, iron oxide, and copper oxide. Of these, manganese oxide and nickel oxide are preferred.

[0040] Examples of the metal salt belonging to the specific periodic d block include inorganic salts such as carbonates, hydrogen carbonates, phosphates, borates, sulfates, and chlorides, and organic salts such as carboxylates. Among them, chlorides are particularly preferred because they are more likely to provide the effects of the present invention.

[0041] For these reasons, the metal compound belonging to the specific periodic d block is particularly preferably a zinc compound, and particularly preferably a zinc chloride salt.

[0042] The molecular weight of the metal compound belonging to the specific periodic d block is usually 100 to 10,000, preferably 150 to 1,000, and particularly preferably 200 to 800, from the viewpoints of dispersibility in the resin composition and productivity. From the standpoint of economy and dispersibility, it is preferable that the metal compound belonging to the specific periodic d block used in the present invention does not include layered inorganic compounds such as montmorillonite and double salts such as hydrotalcite.

[0043] The metal compound belonging to the specific periodic d block may be in any form, such as a solid (powder, fine powder, flakes, etc.), semisolid, liquid, paste, solution, emulsion (aqueous dispersion), etc. Among these, a powder form is preferred because of ease of handling.

[0044] The metal compounds belonging to the specific periodic d blocks may be used alone or in combination of two or more kinds. When multiple types of metal compounds belonging to the specific periodic d blocks are used, the content is the total content, in terms of metal mass, of the multiple types of metal compounds belonging to the specific periodic d blocks.

[0045] The content of the metal compound belonging to the specific periodic d block in terms of metal mass is usually 0.0001 to 1 ppm, preferably 0.005 to 0.75 ppm, and more preferably 0.05 to 0.5 ppm, based on the mass of the resin composition. When the content of the metal compound belonging to the specific periodic d block is equal to or less than the upper limit, the thermal stability tends to be excellent, and when the content is equal to or more than the lower limit, the effects of the invention tend to be excellent.

[0046] The resin composition serving as the basis for the content ratio of the metal compound belonging to the specific periodic d block is a resin composition as a final product containing a PVA resin, a metal compound belonging to the specific periodic d block, a titanium compound, and various additives blended as necessary.

[0047] The content of the metal compound belonging to the specific periodic d block in the resin composition of the present invention in terms of metal can be determined, for example, by heating and incinerating the resin composition, treating it with an acid such as hydrochloric acid, adding pure water to the resulting solution to a constant volume, and measuring the content of the test solution with an atomic absorption spectrometer.

[0048] The mass ratio of the content of the metal compound belonging to the specific periodic d block to the content of the titanium compound in terms of metal is preferably 0.03 to 50,000, more preferably 1 to 10,000, and particularly preferably 6 to 4,000. When the mass ratio is equal to or less than the upper limit, the thermal stability tends to be excellent, whereas when the mass ratio is equal to or more than the lower limit, the molded product tends to be less likely to be discolored.

[0049] Although the reason why the titanium compound and the metal compound belonging to the specific periodic d block are combined in appropriate amounts to obtain excellent effects is unclear, it is believed that the combined use of a specific amount of titanium compound and a metal compound belonging to the specific periodic d block forms an interactant (complex, alloy, etc.), which further interacts with the oxygen of the OH group present in the PVA resin, thereby suppressing the formation of a polyene structure, and as a result, it is presumed that the thermal stability is improved.

[0050] [Other thermoplastic resins] The present resin composition may contain a thermoplastic resin other than the PVA resin within a range that does not impair the effects of the present invention (for example, typically 30 mass% or less of the present resin composition, preferably 20 mass% or less, particularly preferably 10 mass% or less, the lower limit being typically 0 mass%). As the other thermoplastic resin, known thermoplastic resins can be used, such as polyester resins, polystyrene resins, polyvinyl chloride resins, polycarbonate resins, ionomers, polyvinylidene chloride, polyester elastomers, polyurethane elastomers, chlorinated polyethylene, chlorinated polypropylene, etc. These can be used alone or in combination of two or more kinds.

[0051] [Other compounding agents] In addition, the resin composition may contain additives (excluding titanium compounds and metal compounds belonging to a specific periodic d-block) that are generally blended into PVA resins, within a range that does not impair the effects of the present invention, for example, usually 30% by mass or less of the resin composition, preferably 20% by mass or less, particularly preferably 10% by mass or less, the lower limit being usually 0% by mass. Examples of the additives include inorganic double salts (e.g., hydrotalcite, etc.), plasticizers (e.g., aliphatic polyhydric alcohols such as ethylene glycol, glycerin, hexanediol, etc.), oxygen absorbers [e.g., inorganic oxygen absorbers such as aluminum powder and potassium sulfite; ascorbic acid, further its fatty acid esters and metal salts, gallic acid, polyhydric phenols such as hydroxyl group-containing phenol aldehyde resins, terpene compounds, blends of tertiary hydrogen-containing resins and transition metals (e.g., a combination of polypropylene and cobalt), carbon-carbon unsaturated bond-containing resins and Blends with transition metals (e.g., a combination of polybutadiene and cobalt), photooxidative decomposition resins (e.g., polyketones), anthraquinone polymers (e.g., polyvinyl anthraquinone), and the like, and further polymeric oxygen absorbers such as those obtained by adding photoinitiators (e.g., benzophenone) and antioxidants other than those mentioned above and deodorants (e.g., activated carbon) to these blends, heat stabilizers, light stabilizers, ultraviolet absorbers, colorants, antistatic agents, surfactants (excluding those used as lubricants), antibacterial agents, antiblocking agents, and fillers (e.g., inorganic fillers, etc.) may be blended. These compounds may be used alone or in combination of two or more.

[0052] [Method for producing resin composition] The resin composition can be produced by mixing the PVA resin, the titanium compound, and the metal compound belonging to the specific periodic d block by a known method such as a dry blending method, a melt mixing method, a solution mixing method, an impregnation method, etc. Among these, it is preferable to produce the resin composition by a method including a step of melt mixing the resin composition raw material containing the PVA resin and the titanium compound. Also, these production methods can be arbitrarily combined.

[0053] The dry blending method may, for example, be (i) a method in which a pellet-shaped PVA resin is dry-blended with a metal compound and a titanium compound belonging to a specific periodic d-block using a tumbler or the like.

[0054] Examples of the melt mixing method include (ii) a method of melt-kneading a dry blend obtained by dry-blending a pellet-shaped PVA resin with a metal compound and a titanium compound belonging to a specific periodic d block, and (iii) a method of adding a metal compound and a titanium compound belonging to a specific periodic d block to a molten PVA resin and melt-kneading the mixture.

[0055] Examples of the solution mixing method include (iv) a method in which a solution is prepared using a commercially available PVA resin, a metal compound and a titanium compound belonging to a specific periodic d block are mixed therein, the solution is solidified and molded, and then the solid-liquid separation is performed by a known means and the resulting mixture is dried; and (v) a method in which a metal compound and a titanium compound belonging to a specific periodic d block are added to an ethylene-vinyl ester copolymer solution before saponification or a homogeneous solution of PVA resin (such as a water / alcohol solution) during the production process of PVA resin, the solution is solidified and molded, and then the solid-liquid separation is performed by a known means and the resulting mixture is dried.

[0056] The impregnation method may, for example, be (vi) a method in which pelletized PVA resin is contacted with an aqueous solution containing a metal compound and a titanium compound belonging to a specific periodic d block, thereby allowing the metal compound and the titanium compound belonging to the specific periodic d block to be contained in the PVA resin, and then the resin is dried.

[0057] The aqueous solution containing a titanium compound may be an aqueous solution of a titanium compound or a titanium compound immersed in water containing various chemicals to elute titanium ions.

[0058] In the impregnation method, the content (in terms of metal) of the metal compound or titanium compound belonging to the specific periodic d block can be controlled by the concentration of the metal compound or titanium compound belonging to the specific periodic d block in the aqueous solution in which the PVA resin is immersed, the immersion temperature, the immersion time, etc. The immersion temperature and immersion time are usually 0.5 to 48 hours, preferably 1 to 36 hours, and the immersion temperature is usually 10 to 40°C, preferably 20 to 35°C.

[0059] As the drying method in each of the above-mentioned production methods, various drying methods can be used, and either stationary drying or fluidized drying may be used. These methods may also be used in combination.

[0060] As described above, in the present invention, the above-mentioned different methods can be combined. Among them, the melt mixing method is preferred, and method (ii) is particularly preferred, in terms of the productivity and the fact that a resin composition having a more remarkable effect of the present invention can be obtained. In addition, when using the other thermoplastic resins and other compounding agents, they may be compounded by a conventional method according to the above-mentioned production method.

[0061] The present resin composition obtained by each of the above-mentioned production methods may have any shape, but is preferably in the form of pellets. The pellets may be, for example, spherical, oval, cylindrical, cubic, or rectangular, but are usually oval or cylindrical, and from the viewpoint of convenience when used later as a molding material, the size of the pellets is usually 1 to 10 mm, preferably 2 to 6 mm, and more preferably 2.5 to 5.5 mm for the short diameter in the case of an oval shape, and usually 1.5 to 30 mm, preferably 3 to 20 mm, and more preferably 3.5 to 10 mm for the long diameter in the case of a cylindrical shape, from the viewpoint of convenience when used later as a molding material. Also, the diameter of the base is usually 1 to 6 mm, preferably 2 to 5 mm, and the length is usually 1 to 6 mm, preferably 2 to 5 mm. Moreover, it is preferable that the shape and size of the pellet-shaped PVA resin used in each of the above-mentioned production methods are the same.

[0062] The water content of the present resin composition is usually from 0.01 to 0.5% by mass, preferably from 0.05 to 0.35% by mass, and particularly preferably from 0.1 to 0.3% by mass.

[0063] The water content of the resin composition is measured and calculated by the following method. The mass (W1) of this resin composition before drying is weighed on an electronic balance, dried in a hot air dryer at 150°C for 5 hours, and then cooled in a desiccator for 30 minutes, after which the mass (W2) is weighed and calculated using the following formula. Moisture content (mass%)=[(W1-W2) / W1]×100

[0064] In addition, when the present resin composition is in the form of pellets, it is also preferable to attach a known lubricant to the surface of the pellets in order to stabilize the feedability during melt molding. Examples of the lubricant include higher fatty acids having 12 or more carbon atoms (e.g., lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, etc.), higher fatty acid esters (methyl esters, isopropyl esters, butyl esters, octyl esters, etc. of higher fatty acids), higher fatty acid amides (e.g., saturated higher fatty acid amides such as lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, etc.; unsaturated higher fatty acid amides such as oleic acid amide, erucic acid amide, etc.; bis-higher fatty acid amides such as ethylene bis-stearic acid amide, ethylene bis-oleic acid amide, ethylene bis-erucic acid amide, ethylene bis-lauric acid amide, etc.), low molecular weight polyolefins (e.g., low molecular weight polyethylenes having a molecular weight of about 500 to 10,000, low molecular weight polypropylenes, etc., or acid-modified products thereof), higher alcohols having 6 or more carbon atoms, ester oligomers, fluorinated ethylene resins, etc. These compounds can be used alone or in combination of two or more. The content of the lubricant is usually 5% by mass or less, preferably 1% by mass or less, of the resin composition. The lower limit is usually 0% by mass.

[0065] The resin composition thus obtained can suppress thermal degradation when heated, and the remaining amount (%) of the resin composition at 550°C is usually 7.0 mass% or more, preferably 7.5 mass% or more, and more preferably 8.0 mass% or more. The upper limit of the remaining amount (%) at 550° C. is usually 100 mass %. A difference of 1 mass % in the weight loss temperature is very significant since it appears as a large difference in yield in actual production.

[0066] The "remaining amount (%) at 550°C" can be measured using a thermogravimetric analyzer, for example, by the method described in the Examples below.

[0067] [Molding material] The resin composition thus obtained is prepared into various forms, such as pellets, powder, or liquid, and is provided as a molding material for various molded articles. In particular, in the present invention, when the resin composition is provided as a material for melt molding, the effects of the present invention tend to be more efficiently obtained, which is preferable. The present resin composition also includes resin compositions obtained by mixing resins other than the PVA-based resin used in the present resin composition.

[0068] Examples of the molding material include a monolayer film formed from the present resin composition, as well as a multilayer structure having at least one layer containing the present resin composition.

[0069] [Multilayer structure] A multilayer structure according to one embodiment of the present invention (hereinafter referred to as "the multilayer structure") has a layer containing the present resin composition. The layer made of the present resin composition (hereinafter simply referred to as "the present resin composition layer") can be laminated with another substrate (hereinafter, the resin used in the substrate may be abbreviated as "substrate resin") mainly composed of a thermoplastic resin other than the present resin composition to impart further strength, protect the present resin composition layer from the effects of moisture, etc., or impart other functions.

[0070] Examples of the base resin include polyethylene-based resins such as linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-propylene (block and random) copolymers, and ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; polypropylene-based resins such as polypropylene and propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; (unmodified) polyolefin-based resins such as polybutene, polypentene, and polycyclic olefin-based resins (polymers having a cyclic olefin structure in at least one of the main chain and side chain); and polyolefins obtained by treating with an unsaturated carboxylic acid or the like. Examples of the polyolefin resin include polyolefin resins in the broad sense including modified olefin resins such as unsaturated carboxylic acid modified polyolefin resins graft-modified with esters of , ionomers, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, polyester resins, polyamide resins (including copolymerized polyamides), polyvinyl chloride, polyvinylidene chloride, acrylic resins, polystyrene resins, vinyl ester resins, polyester elastomers, polyurethane elastomers, polystyrene elastomers, halogenated polyolefins such as chlorinated polyethylene and chlorinated polypropylene, aromatic or aliphatic polyketones, etc. These can be used alone or in combination of two or more. Incidentally, linear low density polyethylene, low density polyethylene, very low density polyethylene, medium density polyethylene, and high density polyethylene are terms commonly used to represent types of polyethylene.

[0071] Of these, hydrophobic resins such as polyamide-based resins, polyolefin-based resins, polyester-based resins, and polystyrene-based resins are preferred, and polyolefin-based resins such as polyethylene-based resins, polypropylene-based resins, polycyclic olefin-based resins, and unsaturated carboxylic acid-modified polyolefin-based resins thereof are more preferred.

[0072] The layer structure of the present multilayer structure can be any combination such as a / b, b / a / b, a / b / a, a1 / a2 / b, a / b1 / b2, b2 / b1 / a / b1 / b2, b2 / b1 / a / b1 / a / b1 / b2, etc., where a is the resin composition layer and b is the base resin layer. In addition, when R is a recycled layer containing a mixture of the present resin composition and a thermoplastic resin other than the present resin composition, obtained by remelting and molding the ends and defective products generated in the process of manufacturing the present multilayer structure, b / R / a, b / R / a / b, b / R / a / R / b, b / a / R / a / b, b / R / a / R / a / R / b, etc. are also possible. The total number of layers of the present multilayer structure is usually 2 to 15, preferably 3 to 10. In the above-mentioned layer structure, an adhesive resin layer containing an adhesive resin may be interposed between the respective layers, if necessary.

[0073] The adhesive resin may be a known one, and may be appropriately selected according to the type of thermoplastic resin used in the base resin layer "b". Representative examples include modified polyolefin polymers containing carboxy groups obtained by chemically bonding unsaturated carboxylic acids or their anhydrides to polyolefin resins by addition reaction, graft reaction, or the like. Examples of modified polyolefin polymers containing carboxy groups include maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene-propylene (block and random) copolymers, maleic anhydride grafted ethylene-ethyl acrylate copolymers, maleic anhydride grafted ethylene-vinyl acetate copolymers, maleic anhydride modified polycyclic olefin resins, and maleic anhydride grafted polyolefin resins. These may be used alone or in combination of two or more.

[0074] In the present multilayer structure, when an adhesive resin layer is used between the present resin composition layer and the base resin layer, since the adhesive resin layers are located on both sides of the present resin composition layer, it is preferable to use an adhesive resin with excellent hydrophobicity.

[0075] The base resin and adhesive resin may contain conventionally known plasticizers, fillers, clays (montmorillonite, etc.), colorants, antioxidants, antistatic agents, lubricants, core materials, antiblocking agents, waxes, etc., within the range that does not impair the gist of the present invention (for example, 30% by mass or less, preferably 10% by mass or less, based on the total resin). These may be used alone or in combination of two or more kinds.

[0076] The lamination of the present resin composition layer and the substrate resin layer (including the case where an adhesive resin layer is interposed) can be performed by a known method. For example, a method of melt extrusion laminating a substrate resin onto a film, sheet, etc. of the present resin composition, a method of melt extrusion laminating the present resin composition onto a substrate resin layer, a method of co-extruding the present resin composition and a substrate resin, a method of dry laminating the present resin composition (layer) and the substrate resin (layer) using a known adhesive such as an organic titanium compound, an isocyanate compound, a polyester compound, or a polyurethane compound, a method of applying a solution of the present resin composition onto a substrate resin and then removing the solvent, etc. Among these, in consideration of cost and environmental considerations, it is preferable to manufacture the present resin composition layer by providing a step of melt molding, and specifically, a co-extrusion method is preferable.

[0077] The multilayer structure may be subjected to a (heat) stretching treatment as necessary. The stretching treatment may be either uniaxial stretching or biaxial stretching, and in the case of biaxial stretching, it may be simultaneous stretching or sequential stretching. As the stretching method, a method with a high stretch ratio among roll stretching, tenter stretching, tubular stretching, stretch blowing, vacuum pressure molding, etc. may be used. The stretching temperature is a temperature near the melting point of the multilayer structure, and is usually selected from the range of 40 to 170°C, preferably about 60 to 160°C. When the stretching temperature is equal to or higher than the lower limit, the stretchability tends to be excellent, and when it is equal to or lower than the upper limit, a stable stretched state tends to be maintained.

[0078] The multilayer structure after the stretching treatment may be heat-set for the purpose of imparting dimensional stability. Heat setting can be performed by a known means, for example, the multilayer structure after the stretching treatment is heat-treated usually at 80 to 180°C, preferably 100 to 165°C, for usually about 2 to 600 seconds while being kept in a tensioned state.

[0079] When the stretched multilayer structure is to be used as a shrink film, in order to impart heat shrinkability, the above-mentioned heat setting may be omitted, and instead, a treatment such as cooling and setting the multilayer structure after stretching by applying cold air thereto may be carried out.

[0080] The thickness of the present multilayer structure (including the stretched one), and further the thickness of the present resin composition layer, the base resin layer and the adhesive resin layer constituting the multilayer structure, cannot be generally stated depending on the layer structure, the type of base resin, the type of adhesive resin, the application, the packaging form, the required physical properties, etc., but the thickness of the present multilayer structure (including the stretched one) is usually 10 to 5000 μm, preferably 30 to 3000 μm, more preferably 50 to 2000 μm. The present resin composition layer is usually 1 to 500 μm, preferably 3 to 300 μm, more preferably 5 to 200 μm, the base resin layer is usually 5 to 3000 μm, preferably 10 to 2000 μm, particularly preferably 20 to 1000 μm, and the adhesive resin layer is usually 0.5 to 250 μm, preferably 1 to 150 μm, more preferably 3 to 100 μm.

[0081] Furthermore, the thickness ratio of the present resin composition layer to the base resin layer in the present multilayer structure (present resin composition layer / base resin layer) is usually 1 / 99 to 50 / 50, preferably 5 / 95 to 45 / 55, more preferably 10 / 90 to 40 / 60, when there are multiple layers of each, and the thickness ratio of the present resin composition layer to the adhesive resin layer in the present multilayer structure (present resin composition layer / adhesive resin layer) is usually 10 / 90 to 99 / 1, preferably 20 / 80 to 95 / 5, more preferably 50 / 50 to 90 / 10, when there are multiple layers of each ... and the thickness ratio of the present resin composition layer to the adhesive resin layer in the present multilayer structure (present resin composition layer / adhesive resin layer) is usually 10 / 90 to 99 / 1, preferably 20 / 80 to 95 / 5, more preferably 50 / 50 to 90 / 10, when there are multiple layers of each.

[0082] It is also possible to obtain cup- or tray-shaped molded bodies or food packaging bodies using this multilayer structure. In such cases, a squeeze molding method is usually used, specifically, vacuum molding, pressure molding, vacuum pressure molding, plug-assisted vacuum pressure molding, etc. Furthermore, when a tube- or bottle-shaped multilayer container (laminate structure) is obtained from a multilayer parison (a hollow tubular preform before blowing), a blow molding method is used. Specifically, extrusion blow molding (double-head type, mold moving type, parison shift type, rotary type, accumulator type, horizontal parison type, etc.), cold parison type blow molding, injection blow molding, biaxial stretch blow molding (extrusion type cold parison biaxial stretch blow molding, injection type cold parison biaxial stretch blow molding, injection molding in-line type biaxial stretch blow molding, etc.), etc. can be used. The resulting laminate may be subjected to processes such as heat treatment, cooling, rolling, printing, dry lamination, solution or melt coating, bag making, deep drawing, box processing, tube processing, and splitting, as required. EXAMPLES

[0083] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are based on mass.

[0084] Prior to the examples, the following components were prepared. Ethylene-modified PVA resin: Ethylene-modified PVA resin with 4 mol% ethylene structural unit content, melting point of 213°C, and saponification degree of 98 mol% Certain d-block metal compounds: Zinc compound: Zinc chloride (Fujifilm Wako Pure Chemical Industries, Ltd.) Manganese compound: Manganese(IV) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Nickel compound: Nickel(II) oxide (Fujifilm Wako Pure Chemical Industries, Ltd.) Iron compound: Iron chloride hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Titanium compound: Rutile-type titanium(IV) oxide with an average particle size of 5 μm or less (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0085] <Example 1-1> The ethylene-modified PVA resin pellets were dry-blended with the zinc chloride in a metal equivalent content of 0.1 ppm relative to the mass of the resin composition, and the titanium oxide in a metal equivalent content of 0.1 ppm relative to the mass of the resin composition to obtain a mixture. The mixture was then fed to a twin-screw extruder (20 mmφ) equipped with a two-hole die, and extruded under the following extrusion conditions, and the discharged strands were cooled and solidified by air cooling. The solidified strands were then cut by a pelletizer to obtain pellets of the resin composition.

[0086] [Extrusion conditions] Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 =200 / 210 / 225 / 225 / 225 / 225

[0087] <Example 2-1> Pellets of a resin composition were obtained in the same manner as in Example 1-1, except that the content of titanium oxide was changed to 1 ppm, calculated as metal, relative to the mass of the resin composition.

[0088] <Comparative Example 1-1> Pellets of a resin composition were obtained in the same manner as in Example 1-1, except that titanium oxide was not used.

[0089] <Comparative Example 2-1> Pellets of a resin composition were obtained in the same manner as in Example 1-1, except that the titanium oxide content, calculated as metal, was changed to 10 ppm relative to the mass of the resin composition.

[0090] <Comparative Example 3-1> Pellets of a resin composition were obtained in the same manner as in Example 2-1, except that zinc chloride was not used.

[0091] The resulting pellets of the resin compositions of Examples 1-1 and 2-1 and Comparative Examples 1-1 to 3-1 were used to evaluate the thermal stability as described below. The results are shown in Table 1 below.

[0092] [Evaluation of Thermal Stability] Using 5 mg of pellets of the obtained resin composition, the remaining amount (%) at 550° C. was measured using a thermogravimetric analyzer (Pyris 1 TGA, manufactured by Perki Elmer) under conditions of a nitrogen atmosphere, an air flow rate of 20 mL / min, a heating rate of 10° C. / min, and a temperature range of 30 to 550° C. A larger remaining amount (%) at 550° C. means that the thermal stability of the resin composition is superior. The evaluation was carried out based on the following criteria, and the results are shown in Table 1 below. A(good): 7.0% or more B (average): 5.0% or more and less than 7.0% C(poor): 3.0% or more and less than 5.0% D (very poor): Less than 3.0%

[0093] [Table 1]

[0094] As can be seen from Table 1, the resin compositions of Examples 1-1 and 2-1, which contain a metal compound belonging to a specific periodic d block and a specific amount of a titanium compound, had superior thermal stability to the resin composition of Comparative Example 1-1, which does not contain a titanium compound, the resin composition of Comparative Example 2-1, which contains a titanium compound in an amount greater than the specific range, and the resin composition of Comparative Example 3-1, which does not contain a metal compound belonging to a specific periodic d block. The multilayer structures including layers made of the resin compositions of Examples 1-1 and 2-1 also have excellent thermal stability.

[0095] <Example 1-2> The ethylene-modified PVA resin pellets were dry-blended so that the manganese oxide was 0.1 ppm in terms of metal content relative to the mass of the resin composition, and the titanium oxide was 0.1 ppm in terms of metal content relative to the mass of the resin composition, to obtain a mixture. The mixture was then fed to a twin-screw extruder (20 mmφ) equipped with a two-hole die, and extruded under the following extrusion conditions, and the discharged strands were cooled and solidified by air cooling. Next, the solidified strands were cut by a pelletizer to obtain pellets of the resin composition.

[0096] [Extrusion conditions] Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 =200 / 210 / 225 / 225 / 225 / 225

[0097] <Example 2-2> Pellets of a resin composition were obtained in the same manner as in Example 1-2, except that the titanium oxide content, calculated as metal, was changed to 1 ppm relative to the mass of the resin composition.

[0098] <Comparative Example 1-2> Pellets of a resin composition were obtained in the same manner as in Example 1-2, except that titanium oxide was not used.

[0099] <Comparative Example 2-2> Pellets of the resin composition were obtained in the same manner as in Example 1-2, except that the titanium oxide content was changed to 10 ppm based on the mass of the resin composition in terms of metal oxide.

[0100] <Comparative Example 3-2> Pellets of a resin composition were obtained in the same manner as in Example 2-2, except that manganese oxide was not used.

[0101] The obtained pellets of the resin compositions of Examples 1-2 and 2-2 and Comparative Examples 1-2 to 3-2 were used to carry out the following coloration evaluations. The results are shown in Table 2 below.

[0102] [Coloring evaluation] The pellets of the resin compositions obtained in Examples 1-2, 2-2 and Comparative Examples 1-2 to 3-2 were used as samples, and the ratio of the sum of the color numbers "1910" (R: 120, G: 120, B: 104), "1911" (R: 120, G: 120, B: 120), and "1912" (R: 120, G: 120, B: 136) to the sum of the color numbers "1894" (R: 120, G: 104, B: 104) and "1895" (R: 120, G: 104, B: 120) was evaluated using a visual analyzer IRIS VA400 (Alpha mos). ("1910" + "1911" + "1912") / ("1894" + "1895") Color numbers "1894" and "1895" are colors with a deep yellow tint, while color numbers "1910", "1911", and "1912" are colors with a light yellow tint. The greater this ratio, the more suppressed the coloring of the sample. The evaluation was carried out based on the following criteria, and the results are shown in Table 1 below. A(good): 3.5 or higher B(average): 3.0 or more and less than 3.5 C(poor): 2.5 or more and less than 3.0 D(very poor): Less than 2.5

[0103] [Table 2]

[0104] As can be seen from Table 2, the resin compositions of Examples 1-2 and 2-2, which contain a manganese compound and a specific amount of a titanium compound, have a larger proportion of color numbers with a lighter yellow tint than the resin composition of Comparative Example 1-2, which does not contain a titanium compound, the resin composition of Comparative Example 2-2, which contains a titanium compound in an amount greater than the specific range, and the resin composition of Comparative Example 3-2, which does not contain a manganese compound. As a result, discoloration due to thermal degradation is suppressed and the resin compositions of Examples 1-2 and 2-2, which contain a specific amount of a titanium compound, have excellent thermal stability. Incidentally, the multilayer structures including layers made of the resin compositions of Examples 1-2 and 2-2 also suppress coloration due to thermal degradation.

[0105] <Example 1-3> The nickel (II) oxide was dry-blended with the pellets of the PVA resin so that the content in terms of metal was 0.1 ppm relative to the mass of the resin composition, and the titanium oxide was dry-blended with the pellets of the PVA resin so that the content in terms of metal was 0.1 ppm relative to the mass of the resin composition. The mixture was then fed to a twin-screw extruder (20 mmφ) equipped with a two-hole die, and the strands extruded and discharged under the following extrusion conditions were cooled and solidified by air cooling. The solidified strands were then cut with a pelletizer to obtain pellets of the resin composition.

[0106] [Extrusion conditions] Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 =200 / 210 / 225 / 225 / 225 / 225

[0107] <Example 2-3> Pellets of the resin composition were obtained in the same manner as in Example 1-3, except that the titanium oxide content was changed to 1 ppm based on the mass of the resin composition.

[0108] <Comparative Example 1-3> Pellets of a resin composition were obtained in the same manner as in Example 1-3, except that titanium oxide was not used.

[0109] <Comparative Example 2-3> Pellets of a resin composition were obtained in the same manner as in Example 1-3, except that the titanium oxide content, calculated as metal, was changed to 10 ppm relative to the mass of the resin composition.

[0110] <Comparative Example 3-3> Pellets of a resin composition were obtained in the same manner as in Example 2-3, except that nickel oxide was not used.

[0111] The resulting pellets of the resin compositions of Examples 1-3 and 2-3 and Comparative Examples 1-3 to 3-3 were used to evaluate the thermal stability as described below. The results are shown in Table 3 below.

[0112] [Evaluation of Thermal Stability] Using 5 mg of pellets of the obtained resin composition, the temperature (°C) at 5% loss was measured using a thermogravimetric analyzer (Pyris 1 TGA, manufactured by Perki Elmer) under conditions of a nitrogen atmosphere, an air flow rate of 20 mL / min, a heating rate of 10°C / min, and a temperature range of 30 to 550°C. A higher temperature (°C) at 5% loss indicates superior thermal stability of the resin composition. The evaluation was carried out based on the following criteria, and the results are shown in Table 3 below. A(good): 360℃ or higher B (average): 355℃ or higher and less than 360℃ C(poor): 350℃ or higher and less than 355℃ D(very poor): Less than 350℃

[0113] [Table 3]

[0114] As shown in Table 3, the resin compositions of Examples 1-3 and 2-3, which contain a nickel compound and a specific amount of a titanium compound, have superior thermal stability compared to the resin composition of Comparative Example 1-3, which does not contain a titanium compound, the resin composition of Comparative Example 2-3, which contains a titanium compound in an amount greater than the specific range, and the resin composition of Comparative Example 3-3, which does not contain a nickel compound. The multilayer structures including layers made of the resin compositions of Examples 1-3 and 2-3 also have excellent thermal stability.

[0115] <Example 1-4> The ethylene-modified PVA resin pellets were dry-blended with the iron chloride hexahydrate so that the content in terms of metal was 1 ppm relative to the mass of the resin composition, and the titanium oxide was 0.1 ppm relative to the mass of the resin composition, in terms of metal, to obtain a mixture. The mixture was then fed to a twin-screw extruder (20 mmφ) equipped with a two-hole die, and extruded under the following extrusion conditions, and the discharged strands were cooled and solidified by air cooling. Next, the solidified strands were cut by a pelletizer to obtain pellets of the resin composition.

[0116] [Extrusion conditions] Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 =200 / 210 / 225 / 225 / 225 / 225

[0117] <Example 2-4> Pellets of a resin composition were obtained in the same manner as in Example 1-4, except that the titanium oxide content, calculated as metal, was changed to 1 ppm relative to the mass of the resin composition.

[0118] <Comparative Example 1-4> Pellets of a resin composition were obtained in the same manner as in Example 1-4, except that titanium oxide was not used.

[0119] <Comparative Example 2-4> Pellets of the resin composition were obtained in the same manner as in Example 1-4, except that the titanium oxide content was changed to 10 ppm based on the mass of the resin composition in terms of metal oxide.

[0120] <Comparative Example 3-4> Pellets of a resin composition were obtained in the same manner as in Example 2-4, except that iron chloride hexahydrate was not used.

[0121] The resulting pellets of the resin compositions of Examples 1-4 and 2-4 and Comparative Examples 1-4 to 3-4 were used to evaluate the thermal stability as described below. The results are shown in Table 4 below.

[0122] [Evaluation of Thermal Stability] Using 5 mg of pellets of the obtained resin composition, the temperature (°C) at 5% loss was measured using a thermogravimetric analyzer (Pyris 1 TGA, manufactured by Perki Elmer) under conditions of a nitrogen atmosphere, an air flow rate of 20 mL / min, a heating rate of 10°C / min, and a temperature range of 30 to 550°C. A higher temperature (°C) at 5% loss indicates superior thermal stability of the resin composition. The evaluation was carried out based on the following criteria, and the results are shown in Table 4 below. A(good): 345℃ or higher B (average): 340℃ or higher and less than 345℃ C(poor): 335℃ or higher and less than 340℃ D(very poor): Less than 335℃

[0123] [Table 4]

[0124] As can be seen from Table 4, the resin compositions of Examples 1-4 and 2-4, which contain an iron compound and a specific amount of a titanium compound, had superior thermal stability compared to the resin composition of Comparative Example 1-4, which does not contain a titanium compound, the resin composition of Comparative Example 2-4, which contains a titanium compound in an amount greater than the specific range, and the resin composition of Comparative Example 3-4, which does not contain an iron compound. The multilayer structures including layers made of the resin compositions of Examples 1-4 and 2-4 also have excellent thermal stability. [Industrial Applicability]

[0125] Since the resin composition has an improved thermal decomposition temperature during melt molding and has excellent thermal stability and gas barrier properties, it is useful as a packaging material for various foods, as well as for seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, beverages, cosmetics, medical products, etc., and as a material for molded products for packaging pesticides, detergents, civil engineering additives, disinfectants, dyes, pigments, etc.

Claims

1. A resin composition containing a polyvinyl alcohol resin, a titanium compound, and a metal compound belonging to the d block of the 4th period of the long-form periodic table (excluding titanium compounds), the polyvinyl alcohol resin is an ethylene-modified polyvinyl alcohol resin containing 1 to 19 mol % of ethylene structural units, The resin composition has a titanium compound content of 0.0001 to 2 ppm in terms of metal based on the mass of the resin composition.

2. The resin composition according to claim 1, wherein the metal-equivalent content of the metal compound belonging to the d block of the long form periodic table is 0.0001 to 1 ppm based on the mass of the resin composition.

3. The resin composition according to claim 1 or 2, wherein the metal compound belonging to the d block of the 4th period of the long form periodic table is a zinc compound.

4. 3. The resin composition according to claim 1, wherein the content of the titanium compound in terms of metal is 0.0001 ppm or more and less than 1 ppm based on the mass of the resin composition.

5. A molding material comprising the resin composition according to claim 1 or 2.

6. A multilayer structure having a layer comprising the resin composition according to claim 1 or 2.

7. A molded article comprising the multilayer structure according to claim 6.

8. A food package comprising the multi-layer structure of claim 6.

9. A method for producing the resin composition according to claim 1 or 2, A method for producing a resin composition, comprising the step of melt-mixing a resin composition raw material containing the polyvinyl alcohol resin and a titanium compound.

10. A method for producing the multi-layer structure of claim 6, comprising the steps of: A method for producing a multilayer structure, comprising: melt-molding a layer containing the resin composition.

Citation Information

Patent Citations

  • Polyvinyl alcohol fiber and its production

    JP1993222609A

  • Vinyl alcohol-based polymer and composition

    JP2000309607A

  • Polyvinyl alcohol-type polymer film and method for producing same

    WO2013146533A1